2017
DOI: 10.1001/jamafacial.2017.0341
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electrochemical Therapy With Optical, Mechanical, and Acoustic Impedance Properties of Porcine Skin

Abstract: The classic management of burn scars and other injuries to the skin has largely relied on soft-tissue transfer to resurface damaged tissue with local tissue transfer or skin graft placement. In situ generation of electrochemical reactions using needle electrodes and an application of current may be a new approach to treat scars and skin.OBJECTIVE To examine the changes in optical, mechanical, and acoustic impedance properties in porcine skin after electrochemical therapy. DESIGN, SETTING, AND PARTICIPANTSThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
(151 reference statements)
0
27
0
Order By: Relevance
“…Often, these remnants are also injected with lidocaine and epinephrine prior to surgery. This immediate introduction of water can potentially reverse some of the effects of ECT as the primary mechanism of ECT is the localized hydrolysis of water . Some concerns may understandably be raised regarding a potential temperature effect due to resistive heating, but no temperature elevation was measured in this study or any other studies using cartilage, porcine skin, and fat .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Often, these remnants are also injected with lidocaine and epinephrine prior to surgery. This immediate introduction of water can potentially reverse some of the effects of ECT as the primary mechanism of ECT is the localized hydrolysis of water . Some concerns may understandably be raised regarding a potential temperature effect due to resistive heating, but no temperature elevation was measured in this study or any other studies using cartilage, porcine skin, and fat .…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies in our lab have demonstrated collagen structural change in the rabbit cartilage and pig skin [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This study is the first to characterize the redoxinduced alteration in the optical and mechanical behavior in the human skin.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations